Improving Access and Utilization of Maternal Healthcare Services through Focused Antenatal Care in Rural Ghana: A Qualitative Study - Umar Haruna; Gordon Dandeebo; Sylvester Z. Galaa (Advances in Public Health)
Improved access to and utilization of various maternal healthcare services have been seen as the panacea to poor maternal and child health outcomes characterizing many developing countries. Focused Antenatal Care (FANC) replaced the regular antenatal care model about a decade and a half ago. This study sought to document empirical outcomes of how the FANC approach translates access and utilization of maternal health services into positive maternal health outcomes. We utilized a descriptive qualitative design and analysis. We applied key informant interviewing to collect data from 206 respondents consisting of 140 women in their fertility age and 66 health workers across 14 communities in the study district. We found that FANC has been widely implemented across the district with most of the required services integrated into the existing healthcare delivery system. Overall, there has been successful implementation of FANC in the district, resulting in several benefits including the increased utilization of maternal healthcare services, acceptance of family planning, increased skilled delivery, and utilization of postnatal care (PNC) services. This notwithstanding, a number of issues need to be addressed to improve FANC services. These include provision of adequate infrastructure, essential supplies, communication and transportation systems, and manpower and adoption of positive sociocultural practices. No effort should be spared in providing these to sustain the successes and ensure sustainability of FANC.